Soil fertility status and physio-agronomic performance of wheat grown under contrasting tillage and weed management scenarios - DAYAL, PARMESWAR; KUMAR, ARUN; SINGH, MAHENDRA; RANJAN, SHIVANI; SOW, SUMIT; PAL, RAVIKESH KUMAR; TYAGI, SHASHANK; JENA, TWINKLE (Journal of Soil and Water Conservation, 2024)
A field experiment was conducted during winter season of 2021-22 at the Research farm, Bihar Agricultural University, Sabour, Bhagalpur, Bihar to assess the effect of tillage and weed management practices on growth, nutrient uptake, soil fertility status and yield of wheat. The findings showed that with zero tillage, the maximum plant height (98.96 cm) and number of tillers m-2 (398) were discovered. Similarly, at 60 and 90 DAS, respectively, zero tillage recorded the maximum LAI of 3.96 and 2.56, respectively. In comparison to conventional tillage, zero tillage resulted in 4.4%, 4.6%, and 2.4% higher dry matter accumulation at 60, 90 DAS, and harvest stage, respectively. W8 (metsulfuron methyl 20% WP 4 g a.i. ha-1 + clodinafop propargyl 15% WP 60 g a.i. ha-1) demonstrated the highest value among weed management techniques in terms of growth characteristics. In terms of yield, W8 and zero tillage were shown to provide the highest yield. Out of all the tillage techniques, zero tillage showed 14% more soil organic carbon than traditional tillage. At the panicle initiation stage, the maximum bacterial count with zero tillage was 25.48 CFU × 107 g-1 soil, and at harvest, it was 23.26 CFU × 107 g-1 soil. W8 had the notably greatest bacterial population in the soil when it came to weed control techniques. Zero tillage outperformed conventional tillage in terms of nitrogen, phosphorus, and potassium uptake, with increases of 11.2%, 23%, and 14.7%, respectively. The best weed control strategy was W2 (weed free), which had higher nutrient uptake than weedy by 50% (N), 99% (P), and 44.3% (K). W8 was shown to have the most uptake of total nitrogen, phosphorus, and potassium (118.72, 29.05, and 130.89 kg ha-1, respectively) across herbicide combinations. Implementing zero tillage in conjunction with the application of metsulfuron (20% WP 4 g a.i. ha-1) and clodinafop propargyl (15% WP 60 g a.i. ha-1) is recommended to sustain soil fertility and optimize wheat yield.